2018
DOI: 10.1016/j.buildenv.2018.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian-level wind speed enhancement in urban street canyons with void decks

Abstract: The MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters. CitationChew, Lup Wai and Leslie K. Norford. "Pedestrian-level wind speed enhancement in urban street canyons with void decks." Building and Environment 146 (December 2018

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…As shown in Fig. 4, the numerical simulation results of the reference case are in good agreement with the experimental results, which indicates that the selection model calculation parameters are correct (Chew et al 2018). For assessing the air quality of a street canyons, the pollution level at pedestrian height (1.5 m above ground) must be investigated (Ng et al 2014).…”
Section: Validation Of the Modelsupporting
confidence: 63%
See 1 more Smart Citation
“…As shown in Fig. 4, the numerical simulation results of the reference case are in good agreement with the experimental results, which indicates that the selection model calculation parameters are correct (Chew et al 2018). For assessing the air quality of a street canyons, the pollution level at pedestrian height (1.5 m above ground) must be investigated (Ng et al 2014).…”
Section: Validation Of the Modelsupporting
confidence: 63%
“…When the buildings in the central area rise to be the highest one, the horizontal wind speed of pedestrian-level reached the highest speed (Tse et al 2017). Chew et al (2018) used both experimental and numerical methods to investigate pedestrian-level wind speed enhancement with void decks in urban street canyons. The results showed that the enhanced wind speed was beneficial for pollutant dispersion in tropical cities.…”
mentioning
confidence: 99%
“…Binaların geometrik özellikleri, binalar etrafında oluşan hava akışını etkilediğinden, yaya seviyesinde ortaya çıkan istenmeyen rüzgar etkilerini azaltmak için özel bina tasarımları kullanılmaktadır. Binalarda yükseltme yapılarak gerçekleştirilen geometrik değişiklikler, yaya seviyesindeki rüzgar konforunu arttırmaktadır [11,12,13,14]. Yaya konforuna yönelik sayısal çalışmalarda Reynolds Ortalamalı Navier-Stokes (RANS) denklemlerini çözen modeller etkin olarak kullanılmaktadır.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…[1][2][3][4] Low wind speeds promote the accumulation of air contaminants inside street canyons that adversely affect the air quality in an outdoor environment. 5,6 However, too strong wind around a building may cause discomfort or even danger to pedestrians. 7 Thus, to strike a balance is crucial by achieving an acceptable level of wind comfort and allowing an urban area to self-ventilate, but it is rather tricky and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, the benefit of sufficient airflow in the outdoor environment could be significantly diminished and offset by the blockage effects from buildings or other urban structures in an urban setting. 6,[10][11][12] The effect of reduced wind speed is particularly apparent in building wakes and leeward sides of the building. Building shapes and orientations could influence the environmental wind condition, and their proper design can help improve both the perceived wind comfort at pedestrian level 13 and the surface pressure distribution.…”
Section: Introductionmentioning
confidence: 99%